Deficits in Endogenous Adenosine Formation by Ecto-5′-Nucleotidase/CD73 Impair Neuromuscular Transmission and Immune Competence in Experimental Autoimmune Myasthenia Gravis - Laura Oliveira (Mediators of Inflammation, 2015)
AMP dephosphorylation via ecto-5′-nucleotidase/CD73 is the rate limiting step to generate extracellular adenosine (ADO) from released adenine nucleotides. ADO, via A2A receptors (A2ARs), is a potent modulator of neuromuscular and immunological responses. The pivotal role of ecto-5′-nucleotidase/CD73, in controlling extracellular ADO formation, prompted us to investigate its role in a rat model of experimental autoimmune myasthenia gravis (EAMG). Results show that CD4+CD25+FoxP3+ regulatory T cells express lower amounts of ecto-5′-nucleotidase/CD73 as compared to controls. Reduction of endogenous ADO formation might explain why proliferation of CD4+ T cells failed upon blocking A2A receptors activation with ZM241385 or adenosine deaminase in EAMG animals. Deficits in ADO also contribute to neuromuscular transmission failure in EAMG rats. Rehabilitation of A2AR-mediated immune suppression and facilitation of transmitter release were observed by incubating the cells with the nucleoside precursor, AMP. These findings, together with the characteristic increase in serum adenosine deaminase activity of MG patients, strengthen our hypothesis that the adenosinergic pathway may be dysfunctional in EAMG. Given that endogenous ADO formation is balanced by ecto-5′-nucleotidase/CD73 activity and that A2ARs exert a dual role to restore use-dependent neurocompetence and immune suppression in myasthenics, we hypothesize that stimulation of the two mechanisms may have therapeutic potential in MG.